The Role of Epigenetics in the Regulation of Hemostatic Balance - Danese, Elisa; Montagnana, Martina; Gelati, Matteo; Lippi, Giuseppe (Seminars in Thrombosis and Hemostasis, 2020)
Epigenetics, a term conventionally used to explain the intricate interplay between genes and the environment, is now regarded as the fundament of developmental biology. Several lines of evidence garnered over the past decades suggest that epigenetic alterations, mostly encompassing DNA methylation, histone tail modifications, and generation of microRNAs, play an important, though still incompletely explored, role in both primary and secondary hemostasis. Epigenetic variations may interplay with platelet functions and their responsiveness to antiplatelet drugs, and they may also exert a substantial contribution in modulating the production and release into the bloodstream of proteins involved in blood coagulation and fibrinolysis. This emerging evidence may have substantial biological and clinical implications. An enhanced understanding of posttranscriptional mechanisms would help to clarify some remaining enigmatic issues in primary and secondary hemostasis, which cannot be thoughtfully explained by genetics or biochemistry alone. Increased understanding would also pave the way to developing innovative tests for better assessment of individual risk of bleeding or thrombosis. The accurate recognition of key epigenetic mechanisms in hemostasis would then contribute to identify new putative therapeutic targets, and develop innovative agents that could be helpful for preventing or managing a vast array of hemostasis disturbances.
Keywords: primary hemostasis; secondary hemostasis; microRNA; DNA methylation